#### Answer

$\sqrt[3] {y^{2}z}$

#### Work Step by Step

$\sqrt[9] {y^{6}z^{3}}=(y^{6}z^{3})^{1/9}=y^{6/9}z^{3/9}=y^{2/3}z^{1/3}=(y^{2}z)^{1/3}=\sqrt[3] {y^{2}z}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\sqrt[3] {y^{2}z}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.